1990
DOI: 10.1002/j.1556-6676.1990.tb01473.x
|View full text |Cite
|
Sign up to set email alerts
|

Counseling Native Americans

Abstract: This article addresses the issues facing White counselors in providing services to Native Americans, whose values differ significantly from the dominant culture's. Native Americans have been consistently threatened with cultural assimilation. Previously published recommendations to counselors are reviewed and the relevance and possible uses of traditional Native American healing practices are discussed. One such practice, the vision quest, is described in detail. Counselors need to learn culturally relevant me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 9 publications
(6 reference statements)
0
48
0
Order By: Relevance
“…The aim of holistic child and family services is the restoring of harmony (Bourgeois, 1998;Cross, 1997;Fournier & Crey, 1997;Hart, 2001 ). The holistic approach includes the use of natural herbs, traditional ceremonies, song and dance, the vision quest, prayer, the sacred sweat lodge, and the healing circle (Heinrich, Corbine, & Thomas, 1990;McCormick, Neumann, Amundson, & McLean, 1999). The fundamental philosophy underlying holistic healing practices is the interconnectedness of the individual with nature, family, community, society, and the universe (France, 1997;Garrett, & Carroll, 2000).…”
Section: Holistic Perspectivementioning
confidence: 99%
“…The aim of holistic child and family services is the restoring of harmony (Bourgeois, 1998;Cross, 1997;Fournier & Crey, 1997;Hart, 2001 ). The holistic approach includes the use of natural herbs, traditional ceremonies, song and dance, the vision quest, prayer, the sacred sweat lodge, and the healing circle (Heinrich, Corbine, & Thomas, 1990;McCormick, Neumann, Amundson, & McLean, 1999). The fundamental philosophy underlying holistic healing practices is the interconnectedness of the individual with nature, family, community, society, and the universe (France, 1997;Garrett, & Carroll, 2000).…”
Section: Holistic Perspectivementioning
confidence: 99%
“…In four and one-half pages, a literature review using fifty-seven references endeavours to inform nonNative counsellors about Native Americans, touching on aspects of values, acculturation, views of health, vision quests, sweat lodges, and traditional healing in counselling. The authors emphasize the importance of "White" counsellors being aware of their clients' cultural background (including cultural values and meanings), learning about those cultures, and attending cultural events (Heinrich et al , 1990). They conclude that human needs can be met through culture and that minority cultures are not inferior, but may hold values and meanings that are superior, and of which counsellors should be aware (Heinrich et al , 1990).…”
Section: Early Research From the United Statesmentioning
confidence: 99%
“…The authors emphasize the importance of "White" counsellors being aware of their clients' cultural background (including cultural values and meanings), learning about those cultures, and attending cultural events (Heinrich et al , 1990). They conclude that human needs can be met through culture and that minority cultures are not inferior, but may hold values and meanings that are superior, and of which counsellors should be aware (Heinrich et al , 1990). It must be kept in mind that this is a 1990 American article, but is included in this review for bringing to the forefront the need to examine how counselling services are delivered to bo i i ~ clients.…”
Section: Early Research From the United Statesmentioning
confidence: 99%
“…Furthermore, researchers have suggested that many Native Americans hold hostile and suspicious views of White people, so anger is a common emotion in counselling experiences (Heinrich, Corbine, & Thomas, 1990). In order for counselling sessions to reoccur and be positive, counsellors need patience, understanding, acceptance, flexibility, and they must be comfortable with long pauses in conversations, lack o f eye contact, using the Native American family as a resource, and facilitating group work rather than individual work (Heinrich et al, 1990;Herring, 1990).…”
Section: Cross-cultural Counsellingmentioning
confidence: 99%
“…In order for counselling sessions to reoccur and be positive, counsellors need patience, understanding, acceptance, flexibility, and they must be comfortable with long pauses in conversations, lack o f eye contact, using the Native American family as a resource, and facilitating group work rather than individual work (Heinrich et al, 1990;Herring, 1990). Counsellors will also need to work with the Aboriginal client in order to gain their acceptance, trustworthiness, and respect, demonstrate patience, and bring humour into the sessions (Garrett & Garrett, 1994).…”
Section: Cross-cultural Counsellingmentioning
confidence: 99%